After Fukushima: How Do News Media Impact Japanese Public's Risk Perception and Anxiety Regarding Nuclear Radiation. Issue 1 (2nd January 2020) - Guo, Yu; Li, Yiwei; Chen, Liang
ABSTRACT: This study predicts Japanese public's risk perception and anxiety regarding nuclear radiation. These affective reactions are assumed to have direct relationships with subjective knowledge and trust in government, which can be influenced by news media coverage in the post-Fukushima era. Data were collected from a sample of 992 Japanese adults. Results of analyses suggested that trust in news media and subjective knowledge were positive predictors of risk perception. Trust in news media had no direct relationship with anxiety, however, it seemed to contribute to anxiety through the mediating roles of subjective knowledge and risk perception. Trust in government, which was closely related to trust in news media, was a negative predictor of risk perception and anxiety. This study sheds new light on how news media construct perceived reality of environmental risk. Findings may contribute to a more comparative framework to explore whether and how Japan's pattern is unique.